Biologi Sarang Rayap Subfamili Nasutitermitinae di Stasiun Penelitian Suaq Balimbing Taman Nasional Gunung Leuser - Hendra Ervany; Syaukani Syaukani; Husni Husni (Universitas Islam Negeri Ar-Raniry, 2019)
A study had been carried out from May 2017 to February 2018 at Suaq Balimbing Research Center, Gunung Leuser National Park to determine the biology of termite nests of Nasutitermitinae subfamily. The termites were collected with Finding Colony method, while the identification of the termite types and data analysis was conducted in Zoology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Syiah Kuala University. The results found 3 types of termite nests, i.e., (1) arboreal mounds type (N. roboratus, N. matangensis, H. bicolor and N. neoparvus) as an attempt to disguise themselves and protect their colonies from predators; (2) wood nesting type (N. havilandi, N. proatripennis, H. hospitalis, B. neopusillus, L. leucops, and Aciculitermes sp.1) that is built using drywood to form ventilation space between nests, so the nests become sturdier; and (3) subterraneannest type (L. longipes) that has a stronger construction than arborealmounds and wood nesting since it is made of soil attached by saliva liquid. Shapes of termite nest found namely a rounded shape, a cone shape, a shape that fills in hollow trees, a shape that forms a mound on the ground, and rectangular shape. Some of the termites activities were searching for food outside the nest, consuming remaining food in the nest, and making an attack. The identification results showed that there were 18 termites species from 6 genera of Nasutitermitinae subfamily namely Nasutitermes, Hospitalitermes, Leucopitermes, Longipeditermes, Bulbitermes and Aciculitermes.